The Association between Systemic Inflammation and the Prostate Cancer: based on the National Health and Nutrition Examination Survey and Mendelian Randomization Analysis - Guan, Rijian; Wan, Lijun; Zhuang, Changshui (Urology Journal, 2025)
Purpose: The purpose of this combination research was to examine the relationship between systemic inflammation and the risk of prostate cancer (PCa) through the National Health and Nutrition Examination Survey (NHANES) cross-sectional study and two-sample Mendelian randomization (MR) analysis. Materials and Methods: We incorporated NHANES data spanning the years 2001 to 2010, with exposure as systemic inflammation, evaluated using systemic immune-inflammation index (SII) and outcome as PCa, and performed multivariate logistic regression and restricted cubic spline (RCS) to test the correlation between SII and PCa. Further, two-sample MR was used to identify causal associations between specific immune cells and PCa. Results: A total of 7706 participants (age≥40 years) were included in the analysis in the cross-sectional study, including 350 PCa cases, 7356 controls. Higher SII levels were associated with increased odds of PCa (P<.05). The odds ratio (OR) for PCa was 1.51 (95% CI 1.09-2.08) for the highest versus lowest quartile of SII levels in the fully adjusted model. Also, the RCS analysis showed a threshold effect, with SII levels above 8.90 associated with increased odds of PCa. In addition, MR results suggested a causal relationship between CD62L- monocyte, CD62L- HLA DR+ monocyte, CD14+ CD16+ monocyte, CD62L- Dendritic Cell, Monocytic Myeloid-Derived Suppressor Cell, CD28- CD8dim T cell, CD39+ resting CD4 regulatory T cell and PCa (P<.05). Conclusion: This combination analysis provides evidence for a significant causal relationship between systemic inflammation and PCa risk. These findings highlight systemic inflammation and inflammatory immune responses as potential modifiable risk factors for PCa.